MiNDAUS partnership: a roadmap for the cure and management of motor Neurone disease. Issue 5 (3rd July 2022) - Vucic, Steve; Wray, Naomi; Henders, Anjali; Henderson, Robert D.; Talman, Paul; Mathers, Susan; Bellgard, Matthew; Aoun, Samar; Birks, Carol; Thomas, Gethin; Hansen, Catherine; Thomas, Geoff; et al.
Abstract: An innovative approach to patient management, evidence-based policy development, and clinical drug trials is required to provide personalized care and to improve the likelihood of finding an effective treatment for Motor Neurone Disease (MND). The MiNDAus Partnership builds on and extends existing national collaborations in a targeted approach to improve the standard and coordination of care for people living with MND in Australia, and to enhance the prospects of discovering a cure or treatment. Relationships have been developed between leading clinical and research groups as well as patient-centered organizations, care providers, and philanthropy with a shared vision. MiNDAus has established a corporate structure and meets at least biannually to decide on how best to progress research, drug development, and patient management. The key themes are; (i) empowering patients and their family carers to engage in self-management and ensure personalized service provision, treatment, and policy development, (ii) integration of data collection so as to better inform policy development, (iii) unifying patients and carers with advocacy groups, funding bodies, clinicians and academic institutions so as to inform policy development and research, (iv) coordination of research efforts and development of standardized national infrastructure for conducting innovative clinical MND trials that can be harmonized within Australia and with international trials consortia. Such a collaborative approach is required across stakeholders in order to develop innovative management guidelines, underpinned by necessary and evidence-based policy change recommendations, which, will ensure the best patient care until a cure is discovered.